Implementation of the national independent empowerment program - marine and fisheries - Elake Nataniel; Montgomery Warbal; Ignasius Setitit (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to analyze the implementation process of PNPM Mandiri KP by adapting the Top-Down model from Pressman and Wildavsky. This type of research is descriptive with a case study approach. The informants were determined based on the program implementers, namely the Directorate General of Coastal and Small Islands of the Ministry of Maritime Affairs and Fisheries, the Department of Marine Affairs and Fisheries, Maluku Province, Buru Regency, and Central Maluku Regency, as well as related agencies. Meanwhile, informants from receiving community groups were determined purposively. Data analysis using NVIVO. The results of the research are formulated in three propositions, namely: (1) the process of implementing public policies can create changes, both in the behavior of social, economic, and cultural status towards implementation in the field or target groups determined by the policy context and content included in the policy document. (2) The policy implementation process with a long bureaucratic span will tend to fail if internal and external coordination are not fully understood and carried out consistently by policy implementers. (3) Top-down policy implementation will be successful if it can be interpreted and adapted to local conditions where the policy is implemented.